Spatial distribution and contamination assessment of heavy metals in marine sediments of the southern coast of Sfax, Gabes Gulf, Tunisia. (June 2018) - Naifar, Ikram; Pereira, Fernando; Zmemla, Raja; Bouaziz, Moncef; Elleuch, Boubaker; Garcia, Daniel
Abstract: In order to investigate the current distribution of metal concentrations in surface marine sediments of the southern coast of Sfax (Tunisia), thirty-nine samples were collected in the vicinity of a mixed industrial and domestic wastewater effluent discharge. In comparison with the threshold effect level and probable effect level, the majority of metals had high ecological and biological risks. Enrichment factor and geoaccumulation Index showed that the majority of sediments are unpolluted by As, Ni and Pb, moderately polluted by Cr and Cu and moderately to strongly polluted by P, Y, Zn. Besides, all sites are extremely polluted by Cd. Principal component analysis indicates that As, Cu and Ni were mainly from lithogenic sources, whereas Cd, Cr, F, P, Pb, Y and Zn were mainly derived from anthropogenic source. Findings of this research can be used as suitable reference for future studies and environmental management plans in the region. Highlights: The surface marine sediments of the southern coast of Sfax were polluted by heavy metals. SQGs indicated high ecological and biological risk to the coast of Sfax. Cd, Cr, Pb, Zn and Y were mainly derived from anthropogenic input. P, F and heavy metals originate from the same source. Sediment metallic contamination is due to the phosphate treatment plant of Sfax.